Two highly reddened young open clusters located beyond the Saggitarius arm - Piatti, Andres Eduardo (2002)
We present the results of CCD BVI Johnson-Cousins photometry down to V = 19 mag in the regions of the unstudied stellar groups Pismis 23 and BH 222, both projected close to the direction to the Galactic centre. We measured V magnitudes and B-V and V-I colours for a total of 928 stars in fields of 4'x4'. Pismis 23 is conclusively a physical system, since a clear main sequence and other meaningful features can be seen in the colour-magnitude diagrams. The reality of this cluster is also supported by star counts carried out within and outside the cluster field. For Pismis 23 we derive colour excesses E(B-V) = 2.0 +/- 0.1 and E(V-I) = 2.6 +/- 0.1, a distance from the Sun of 2.6 +/- 0.6 kpc (Z = -0.19 pc) and an age of 300 +/- 100 Myr (assuming solar metal content). BH 222 appears to be a young open cluster formed by a vertical main sequence and by a conspicuous group of luminous, typically red supergiant stars. We derived for this cluster a colour excess E(V-I) = 2.4 +/- 0.2, a distance from the Sun of 6.0 +/- 0.7 kpc (Z = -0.46 pc) and an age of 60 +/- 30 Myr. The resulting reddening and distance estimates place these two young objects among the most reddened and distant open clusters known in the direction towards the Galactic centre. They are located beyond the Sagiattarius arm, close to the direction where this arm probably bifurcates into two arms.